2015
DOI: 10.4066/amj.2015.2258
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and patterns of hearing loss among chronic kidney disease patients undergoing haemodialysis

Abstract: Mild sensorineural hearing loss is common in CKD. Hearing loss has no specific pattern as it prevails at high and low frequencies. Hearing loss may be inversely associated with the number of haemodialysis sessions but not with duration of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 16 publications
2
17
1
Order By: Relevance
“…Finally, hearing loss might result from toxic influence of aluminum on inner ear in these patients [8]. In addition to that, it was reported that duration of hemodialysis constituted the only independent predictor of SNHL [6].…”
Section: Sensorineural Hearing Loss (Snhl)mentioning
confidence: 86%
See 4 more Smart Citations
“…Finally, hearing loss might result from toxic influence of aluminum on inner ear in these patients [8]. In addition to that, it was reported that duration of hemodialysis constituted the only independent predictor of SNHL [6].…”
Section: Sensorineural Hearing Loss (Snhl)mentioning
confidence: 86%
“…Sensorineural hearing loss (SNHL) is a common otorhinolaryngological manifestation in patients with CKD [6,7]. CKD is believed to be an important independent risk factor for SNHL [6,7].…”
Section: Sensorineural Hearing Loss (Snhl)mentioning
confidence: 99%
See 3 more Smart Citations